If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a(3 + x + -2b) = c(dx + -2) Reorder the terms: a(3 + -2b + x) = c(dx + -2) (3 * a + -2b * a + x * a) = c(dx + -2) (3a + -2ab + ax) = c(dx + -2) Reorder the terms: 3a + -2ab + ax = c(-2 + dx) 3a + -2ab + ax = (-2 * c + dx * c) 3a + -2ab + ax = (-2c + cdx) Solving 3a + -2ab + ax = -2c + cdx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Reorder the terms: 3a + -2ab + ax + 2c + -1cdx = -2c + 2c + cdx + -1cdx Combine like terms: -2c + 2c = 0 3a + -2ab + ax + 2c + -1cdx = 0 + cdx + -1cdx 3a + -2ab + ax + 2c + -1cdx = cdx + -1cdx Combine like terms: cdx + -1cdx = 0 3a + -2ab + ax + 2c + -1cdx = 0 The solution to this equation could not be determined.
| -7x+10(x-6)=9(3x+4) | | (X-2)+(3x-7)+(5x)=180 | | -n(5n+8)+8(n+2)= | | 8+y^2=2*16 | | -2+m=20 | | -8(v-3)-4v=120 | | 9x^2-18xy-8x+16y= | | 10x-20+7=12+6x+3 | | -5.6+8a=7a+7.6 | | -8-(-16+10)=12 | | 7x(1-4x)+5(1+2x)= | | (x^2+6x+5)+(x^2+6x+5)= | | 6x-4=16+2x | | 3/2x-y=17 | | 4m-4=rm | | 2x-6=3x+1-x-6 | | x-3/2y=13 | | -13=8m+5m | | X+(x-1)+(x+1)=90 | | 2v+3=19 | | 3(-4x)=-2(6x-9) | | 3(y-4)-4=2y+6.9 | | (-.8)(1/5)=x | | 8y=11y+3 | | w/11=3 | | 6+2(8f-2)=4(1+f) | | 6.2x-5+x-1.5=0 | | p=180*(33.333/100) | | (-4)-(-.8)=x | | (x^2+6x-4)+(-x^2-6x+4)= | | 91+(-11)= | | 5y^2+y+1y=4 |